Sistemas deliberativos no contexto da gestão social: a abordagem dos subsistemas aplicada aos conselhos de políticas públicas em Pará de Minas-MG - Fonseca, Geraldo Magela (2019)
In conformity with recent studies on the deliberative system, and seeking to contribute with this theory, this research presents the analysis of a public policy council subsystem. Inside the Social Management context, the theoretical background sought its definition and synthesis in the debate between this new form of management and Management Administration. It also discussed the debate between democratic theories and participatory institutions and their democratizing characteristics. This scenario supports this study of deliberative subsystems using social network analysis techniques to evaluate the level of connection between the subsystem formed by the public policy councils in Pará de Minas, Minas Gerais. Despite of replicating an experiment devoloped by Silva and Ribeiro (2016) in the Belo Horizonte’ public policy council subsystem, the present work expanded the study collecting primary data through a controlled questionnaire done with the council’s members, which sought to verificate if the informal relationships between members increases the connection between the councils. Through the analysis of the network, it was possible to verify which areas of this subsystem are connected, which councils are more attractive and which are the most active council’s members, denoting greater centrality by some elements. It was possible to verify that the impersonal relationships between the counselors are capable of strengthening the connection between the councils and increase the possibilities to the members to influence each other, this relation produce a tendency in the council’s decisions to be more consolidated. A fully connected subsystem improves the condition to the exercise of participation and deliberation, enhancing the inclusion of citizens in the deliberation process and making viable the experience of Social Management.